Darkness of Love as Portrayed in Ernest Hemingway’s Hills Like White Elephant - Fifit Rizkiyani; Faza Lutfiyana (Journal of English Language Studies, 2017)
In this paper, the writers tried to analyze a ‘message’ that is delivered by the author. The purpose of this writing is to investigate how the author portrays ‘darkness of love’ through literary works. This research uses formulaic literature approach as the theory and methodology. It  contains the description,  analysis,  and  interpretation  of  these  data  supported  by  theories. By doing depth analysis of ‘hills like white elephant’s’ stories and its figurative language, the result showed that the phrase ‘darkness of love’ caused by forbidden love. Keywords: darkness of love, ernesthemingwa; formulaic literature; hills like white elephant